Optimization of chlorophyll extraction from Gynura Procumbens - Zainal Abidin, Zurina; Mohamad, Wan Noraznorin; Samadi, Mahtab (Malaysian Analytical Sciences Society, 2016)
Herb is a famously used as medicinal plant as an alternative to chemicals based medicine since it is safer. Gynura Procumbens (sambung nyawa) is bicolor (green and red) herbal plant which is widely grown in Asia. Recent studies proved that this plant has anti-herpes simplex virus, anti-flammatory and antihyperglycaemic properties. This work investigated the extraction of chlorophyll a and b from gynura procumbens of green-leaf species. Optimization was done both by experiment and also Response Surface Method. Solid liquid extraction was used to extract the chlorophyll a and b. The solid to solvent ratio, temperature, solvent used and extraction time were varied to determine the optimum conditions for extraction. It was found that at 80C in 90 minutes with 2:5 solid to solvent ratio were the most favorable conditions to extract chlorophyll a and b. Five valuable compounds was found from GC-MS analysis which are 2-Hexanal, Phenol, Oleic Acid, Copaene and Phytol. This implies that Gynura Procumbens promises a good source of many useful bioactive compounds.